The Influence of Brand Image and Product Quality Towards Customer Satisfaction Among High School Students Using Xiaomi Brand - Widodo, Arif Siaha; Hady, Hamdy; Muharam, Hari (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
This research aims to test how big the influence of branding is on customer satisfaction. To test how much influence product quality has on customer satisfaction . To test how big the influence of brand and product quality is on customer satisfaction among high school students using Xiaomi brand smartphones in the city of South Tangerang. . The method approach used in this research is a quantitative approach. The population used in this research were S LTA students using Xiaomi brand smartphones in South Tangerang City. The sample consisted of 388 respondents. The sampling technique uses accidental sampling using the Slovin formula in determining the number of samples. Meanwhile, the data analysis method tests research instruments using validity tests, reliability tests. Data analysis techniques consist of descriptive analysis of respondent characteristics and SEM Lisrel analysis. The results of this research show that (1) Brand image has positive and significant effect on customer satisfaction (2) Product quality has positive and significant effect on customer satisfaction (3) Brand image and product quality simultaneously has positive and significant effect on customer satisfaction